Targeting Exocytosis: Ins and Outs of the Modulation of Quantal Dopamine Release - Westerink, Remco H.S. (CNS & Neurological Disorders - Drug Targets, 2006)
Dopaminergic neurotransmission is mediated by the vesicular release of dopamine (DA), i.e. DA exocytosis. DA exocytosis and its modulation are generally believed to affect neuronal communication, development, maintenance and survival, and contribute to extracellular DA levels in the brain. As a result, DA exocytosis likely plays an important role in several neurological and psychiatric disorders, like Parkinson's disease (PD) and schizophrenia. As exocytosis is part of a sophisticated ensemble of processes, it can be modulated at different levels, including DA synthesis, uptake and vesicular transport as well as Ca2+-homeostasis and exocytotic proteins. Nonetheless, to be effective, modulation of exocytosis should result in functional changes, which are reflected by changes in release frequency, vesicle contents, and the time course of the exocytotic event. As will be shown in this review, functional changes in DA exocytosis can be produced by e.g. pharmacological/drug treatment, feedback mechanisms and up/down-regulation of exocytosis-related proteins. Moreover, the mode of DA exocytosis, i.e. classical full fusion or kiss-and-run exocytosis, could also serve as a potential target for functional modulation of dopaminergic neurotransmission. Since the onset and progression of neurological and psychiatric disorders often show a strong correlation with changes in brain DA levels, DA synthesis, transport or uptake, the findings described in this review highlight the importance of the modulation of (the mode of) DA exocytosis for normal progression of dopaminergic neurotransmission and the potential of exocytotic processes as drug targets.
Keywords: calcium homeostasis